Perancangan dan Pembuatan Vıdeo Profıle Nagaya Pangkas Om Boy - Jimmy Pratama; Frenky Frenky (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2021)
Barbershop as a service or business that offers facilities to consumers or customers to meet ongoing primary needs. The increasing development of barbershops in Bengkong is a testament to the awareness of men in maintaining their appearance. With the barbershop business in Bengkong, it causes competition in the business, especially in Nagaya Pangkas Om Boy’s, increase and decrease in the number or customers is not stable every month so that it has an impact on income. The problem obtained in this research is that Nagaya Pangkas Om Boy's business needs a company profile video to provide information to consumers or customers. The purpose of this research is to help Nagaya Pangkas Om Boy's efforts to promote and provide information to the public about the business of Nagaya Pangkas Om Boy's barbershop. The research method used is Multimedia Development Life Cycle (MDLC) with the stages, namely concept, design, material gathering, assembly, testing, and distribution. The result of this research is a company profile video which is implemented into social media Youtube and Instagram.